2010
DOI: 10.1103/physrevb.81.024112
|View full text |Cite
|
Sign up to set email alerts
|

Ordered magnesium-lithium alloys: First-principles predictions

Abstract: Magnesium-lithium ͑Mg-Li͒ alloys are among the lightest structural materials. Although considerable work has been done on the Mg-Li system, little is known regarding potential ordered phases. A first and rapid analysis of the system with the high-throughput method reveals an unexpected wealth of potentially stable low-temperature phases. Subsequent cluster expansions constructed for bcc and hcp superstructures extend the analysis and verify our high-throughput results. Of particular interest are those structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…IV. Occasionally, fully relaxed calculations by Aflow (cell volume and shape and the basis atom coordinates inside the cell) turn up as ground state structures that do not yet have known experimental prototypes [7,[16][17][18][19][20][21][22][23][24][25]. When identified, they are also added to the structure database.…”
Section: Software and Structure Databasementioning
confidence: 99%
See 1 more Smart Citation
“…IV. Occasionally, fully relaxed calculations by Aflow (cell volume and shape and the basis atom coordinates inside the cell) turn up as ground state structures that do not yet have known experimental prototypes [7,[16][17][18][19][20][21][22][23][24][25]. When identified, they are also added to the structure database.…”
Section: Software and Structure Databasementioning
confidence: 99%
“…The HT concept has already become an effective and efficient tool for materials discovery [1][2][3][4][5][6][7][8] and development [9][10][11][12][13]. Examples of computational materials HT applications include combinatorial discovery of superconductors [1], Pareto-optimal search for alloys and catalysts [14,15], data-mining of quantum calculations applying principle-component analysis to uncover new compounds [5][6][7][16][17][18][19][20][21][22][23][24][25], Kohn-anomalies search in ternary lithiumborides [26][27][28], and multi-optimization techniques used for the study of high-temperature reactions in multicomponent hydrides [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This includes most of the transition metals and several other alloys including some of industrial importance (e.g., Al, Ca). Although also systems of interest, Ag-Mg, Hf-Mg, InMg, and Li-Mg were not included because one or more of the authors have already reported HT ab initio data on these systems 5,10,11,22 . In the systems Al-, Ge-, and Si-Mg, anomalously low energies (many meV below the next lowest energies) were obtained for the Be 2 Zn structure.…”
Section: A Structure Librarymentioning
confidence: 99%
“…A notable exception is the Mg-Li system, in which an fcc solid solution is stabilized with only 30 at.% Li. [1][2][3] Under non-bulk thermodynamic constraints (i.e. in thin film or nano-structures), phase stability can be modified through the introduction of coherency constraints [4] and it is likely that Mg-based solid solutions with a wider range of alloying elements can be stabilized.…”
mentioning
confidence: 99%